FACTORS AFFECTING TOBIN'S Q COAL MINING COMPANY REGISTERED IN INDONESIA STOCK EXCHANGE - E. Batara Manurung; Hermanto Siregar; Imam Teguh Saptono (School of Business, IPB University (SB-IPB), 2016)
The purpose of this study is to examine the effect of capital structure (debt to asset ratio and debt to equity ratio), economic value added, and coal reserves towards Tobin’s Q, as a proxy of firms’ value, of coal companies listed on the Indonesia Stock Exchange (IDX). This study also aims to examine the contribution of Tobin’s Q towards sectoral stock index price of coal production companies. From a total population of 23 companies, this study took a sample of 16 coal production companies using purposive sampling method. The data used is collected from the companies audited financial statements and annual reports in IDX’s website from 2009 to 2014. The results of multiple linear regression analysis show that there is significant impact of economic value added, coal reserves and profitability dummy towards Tobin’s Q. Furthermore, the results of linear regression analysis show that there is significant impact of Tobin’s Q towards sectoral stock index price of coal production companies. Based on the results of this study, the financial decision makers in coal production companies are advised to use economic value added, availability of coal reserves and profitability in improving firm value reflected in its share price.Keywords: capital structure, coal reserves, economic value added, Tobin’s Q